Efeito da inserção de nanopartículas sintéticas preparadas por rota coloidal em matriz acrílica comercial de uso odontológico - Souza Neto, Francisco Nunes de (Universidade Federal de São Carlos, 2016)
Acrylic resins are very used in dentistry to dental restorations and manufacture of prostheses. New compositions of acrylic resin have been developed through the incorporation of silver nanoparticles due to the antimicrobial potential. In this study, silver nanoparticles were synthesized and employed in the preparation of nanocomposites with polymethylmethacrylate (PMMA). PMMA-Ag nanocomposites were synthesized and characterized by structural, thermal, mechanical and biological techniques in order to evaluate the influence of these nanoparticles on the physicochemical properties of the new formed materials. PMMA-Ag nanocomposites were synthesized with the addition of 0.05, 0.5 and 5% (l/l) of silver nanoparticles in the polymer during the plastic phase. Possible interactions between nanoparticles and polymeric matrix occurred through the carboxylate ions, resulting in a gain in the thermal stability due to the barrier effect, which slows down the degradation of nanocomposites. The nanocomposites showed a heterogeneous distribution of spherical particles in the polymeric matrix. The mechanical tests showed the nanocomposites presented low storage modulus, loss modulus and tan δ values, which are characteristic of materials which exhibit an interfacial interaction between inorganic nanoparticles with polymer matrix. Clinically, the nanocomposites can be applied in dentistry, according to the normative American Dental Association (1958), through its specification No. 12 and ISO 4049, which evaluate the mechanical properties of dental materials. These results showed statistically are not difference between nanocomposites and the polymeric matrix. The microbiological adhesion test of PMMA and its nanocomposites to combat Candida glabrata revealed the nanocomposite with a lower percentage of colloidal solution have higher fungicide activity.
Effect of the insertion of synthetic nanoparticles prepared by colloidal route in a commercial acrylic matrix of dental use
Keywords: Polimetacrilato de metila; Nanopartículas de prata; Nanocompósitos; Antimicrobianos; CIENCIAS EXATAS E DA TERRA::QUIMICA